PENERAPAN BIAYA RELEVAN DALAM PENGAMBILAN KEPUTUSAN MEMBUAT SENDIRI ATAU MEMBELI DARI LUAR PADA CV. MAKMUR JAYA. - Lailatus Sa’adah (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2017)
Decision-making is one of the most important functions by the management especially if decision-making requires such costs as relevant costs. Information on the relevant costs becomes an important thing that the company always needs in making the right decision. Every decision taken by the management will be a benchmark of success of a company in the future. Relevant Costs represent a different future cost on each alternative. All decisions relate to the future. Therefore, only future costs can be relevant to the decision. However, to be relevant, a cost must not only be a future cost, but it must also be different from one alternative to another. The purpose of this study is to analyze the relevant costs in relation to making decisions on their own or buying from outside. The method of analysis used is quantitative descriptive method. The results show the company has not been maximized in applying the relevant cost in making the decision to make your own or buy from the outside. Company management should apply relevant cost calculations in order to make informed decisions on available alternatives. Keywords: Relevant cost, make your own, buy from outside.